The Effect Of Bpjs Health Policy Implementation On The Quality Of Service And Its Impact On Satisfaction And Compliance Of Bpjs Participants In Malang City (International Journal of Scientific Research and Management (IJSRM), 2021)
The purpose of this research is 1) testing and analyzing the effect of the implementation of BPJS health policies on service quality in Malang City, 2) testing and analyzing the implementation of BPJS health policies on the satisfaction of BPJS participants in Malang City, 3) testing and analyzing the implementation of BPJS health policies on satisfaction of BPJS participants in Malang City , 4) testing and analyzing the quality of service on the satisfaction of BPJS participants in Malang City. 5) testing and analyzing the quality of service to the compliance of BPJS participants in Malang City, 6) testing and analyzing the quality of satisfaction with the compliance of BPJS participants in Malang City. The type of research that will be used in this research is explanatory research, while the research method used is a survey method. Data analysis techniques using Smart PLS software.